1983
DOI: 10.1136/hrt.49.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive quantification of aortic regurgitation by Doppler echocardiography.

Abstract: SUMMARY This study was undertaken to assess the contribution of Doppler echocardiography to the quantification of aortic valve regurgitation. Ultrasound examination was performed by recording aortic arch blood flow from the suprasternal notch. A non-invasive index of valve regurgitation was obtained by calculating the ratio between the maximal amplitude of forward flow during systole and the amplitude of retrograde flow during diastole measured at the onset of the R wave of the electrocardiogram. This index wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…According to Pearson correlation analysis their correlation was very significant (r=0.69, p<0.001). Previous studies showed that forward and reverse flow profiles in the ascending aorta can be irregular and unreliable (12,13). However, there are other studies showing that descending aorta velocity profile was more reliable (14,15).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…According to Pearson correlation analysis their correlation was very significant (r=0.69, p<0.001). Previous studies showed that forward and reverse flow profiles in the ascending aorta can be irregular and unreliable (12,13). However, there are other studies showing that descending aorta velocity profile was more reliable (14,15).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have reported a good correlation between severity of aortic regurgitation and Doppler assessment of flow velocity at the end of diastole in the descending aorta just beneath the aortic isthmus (11)(12)(13)(14). Also descending aorta velocity profile was more reliable than ascending aorta (15).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In Adult Cardiology, QDP was used for the evaluation of the retrograde diastolic flow in aortic arch as an indirect method for the evaluation of the severity of aortic insufficiency [3]. The QDP was of help regarding the PW SVP for the reflux evaluation and analysis of the turbulent flow.…”
Section: (A) (B)mentioning
confidence: 99%
“…In the present work, this technology was tested in vitro as well as in different clinical applications and in different vessels, with a variety of transducer typologies. The considered clinical studies were: Vascular, regarding both arteries and veins at the neck district level (Common Carotid Artery -CCA, Internal Jugular Vein -IJV and Vertebral Vein VV) [1] Cardiology, regarding both Adult and Pediatric (Aorta and Inferior Vena Cava -IVC) [2][3] Obstetrics, about the study of uterine arteries in pregnancy [4][5] In all cases, QDP was used together with classic Doppler technologies such as PW and Color Doppler (CD), as well as a stand-alone Doppler tool. Longitudinal scanning of the examined vessels was considered with linear and convex transducers.…”
Section: Introductionmentioning
confidence: 99%